Hubungan Beban Kerja Mental dan Kelelahan Kerja dengan Stres Kerja pada Perawat Shift Malam Rumah Sakit Islam Fatimah Banyuwangi - Aminulloh, Sandi; Tualeka, Abdul Rohim (Media Gizi Kesmas, 2024)
Background: Every company is obliged to implement Occupational Safety and Health (K3) in the workplace. Implementation of this concept is the most important step to ensure work safety, protect workers and promote a higher level of health, so that workers can avoid various risks that endanger workers. One of the dangers at work is the psychological aspect, namely work stress. The American National Institutes of Health states that nursing is a job at risk of experiencing work stress at number 27 out of 130 types of work. The high workload on nurses can fluctuate the work stress experienced by them. Objective: This study aims to find the relevance or relationship between gender, length of service, mental workload, age, and work fatigue with work stress in nurses in the night shift work system at the emergency installation at the Banyuwangi Islamic Fatimah Hospital. Method: This research is quantitative with statistical analysis of the Spearman correlation coefficient. Results: The results of the study showed that there was no relationship between age, gender, years of work, mental workload and work stress. In addition, a relationship was found between work fatigue and work stress. Conclusion: Overall, it can be concluded that age, gender, length of service and workload for nurses are not related to work stress. However, the work fatigue of nurses at Fatimah Banyuwangi Islamic Hospital is related to the nurses' work stress.